THE CORRELATION BETWEEN ESTRADIOL LEVELS WITH TELOMERE LENGTH BASED ON HISTORY OF USING HORMONAL CONTRACEPTIVE IN PREMENOPAUSAL WOMEN - Yusrawati; Sulastri, Delmi; Desmawati (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study aimed to investigate the correlation between nutritional status and estradiol level with telomere length in premenopausal women with and without hormonal contraceptive history. Methods: This cross-sectional study was conducted in Padang city to 115 premenopausal Minangkabau ethnic 40â€“54 years old. Height examined using stature meter, waist circumference (WC) using measuring tape, and body weight using body scale were performed by trained people. Blood sample analysis was performed using O'Callaghan and Fenech's technique to measure telomere length. Estradiol level was measured by enzyme-linked immunosorbent assay technique. Results: This research indicated that an average telomere length was 552.96Â±422.57 bp, body mass index (BMI) was 26.12Â±4.84, WC was 85.66Â±10.28 cm, and estradiol level was 148.24Â±54.03 pg/ml. The proportion of subjects who have hormonal contraceptives history was 65.2% with the most method of contraceptive used injection (75%). There were no correlations between BMI, WC, and estradiol level with telomere length (p>0.005). However, there was a positive significant correlation between estradiol levels and telomere length in women with no history of hormonal contraceptive use (p=0.025). Conclusion: A history of hormonal contraceptive used influences the correlation between estradiol levels and telomere length in premenopausal women.Â